2019
DOI: 10.1002/kjm2.12022
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of caveolin‐1 as a slow‐release material on bone‐tendon junction healing: A comparative study

Abstract: Bone tendon junction injury is hard to cure because of its special anatomical structure, and the treatment applied for bone‐tendon junction injury cannot result in the perfect vascular regeneration and restoration of the fibrocartilage zone. In this article, we aim to explore the effect of caveolin‐1 as a slow‐release material on bone‐tendon junction healing. Seventy‐two New Zealand rabbits were randomly selected and assigned into the experimental, sham‐operated and control groups (n = 24). Caveolin‐1 microsph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The subsequent results of this study revealed that Caveolin-1 knockdown could promote bone-tendon healing, improve biomechanical properties, and reduce the rupture risk of injured tendon after RCT in rats. In accordance with this finding, a recent work has demonstrated that Caveolin-1 can enhance biomechanical properties and accelerate bone-tendon junction healing by promoting the formation of the transition zone (Liang et al 2019). In addition, the in vitro data suggested that Caveolin-1 knockdown suppressed the adipogenic differentiation of TSCs via activation of the cAMP/PKA pathway.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The subsequent results of this study revealed that Caveolin-1 knockdown could promote bone-tendon healing, improve biomechanical properties, and reduce the rupture risk of injured tendon after RCT in rats. In accordance with this finding, a recent work has demonstrated that Caveolin-1 can enhance biomechanical properties and accelerate bone-tendon junction healing by promoting the formation of the transition zone (Liang et al 2019). In addition, the in vitro data suggested that Caveolin-1 knockdown suppressed the adipogenic differentiation of TSCs via activation of the cAMP/PKA pathway.…”
Section: Discussionsupporting
confidence: 60%
“…Caveolin-1 is known as an oncogenic membrane protein related to endocytosis, extracellular matrix organization, cholesterol distribution, cell migration and signaling (Nwosu et al 2016). Caveolin-1 can function as a slow-release material to accelerate bone-tendon junction healing via promoting the formation of the transition zone (Liang et al 2019).…”
Section: Introductionmentioning
confidence: 99%